HAK DAN KEWAJIBAN KONSUMEN DALAM ASURANSI PERSPEKTIF UNDANG-UNDANG PERLINDUNGAN KONSUMEN - Daimul Hidayah (Institut Agama Islam Hasanuddin Pare, 2024)
Insurance is a form of agreement that provides financial protection to consumers against various risks that have been agreed upon in the policy. In the legal context in Indonesia, the relationship between consumers and insurance companies is regulated by the Consumer Protection Law (UUPK) which aims to provide legal protection, justice, and a balance of rights and obligations between the two parties. This article aims to analyze the rights and obligations of consumers in insurance agreements based on the UUPK, with a focus on potential violations that occur and legal protection efforts that can be made. This study uses a normative juridical method with a statutory approach and conceptual analysis. The data sources used are secondary data, in the form of literature reviews, legal documents, court decisions, and related regulations. The UUPK explains that consumers have the right to comfort, security, and safety in using products or services, including insurance. Consumers also have the right to obtain correct, clear, and honest information regarding the benefits, risks, and provisions of the insurance policy. On the other hand, consumers are obliged to pay premiums according to the agreement, provide accurate information regarding the object or subject of insurance, and comply with the provisions stated in the policy. However, the results of the analysis indicate that there are problems that often occur in insurance practices. Violations of consumer rights generally include a lack of transparency of information from insurance companies, unilateral rejection of claims that are not in accordance with the agreement, and the preparation of standard clauses that are detrimental to consumers. On the other hand, consumer non-compliance with obligations, such as negligence in paying premiums or hiding information, are also factors that trigger disputes. This article emphasizes the importance of the government's role in conducting stricter supervision of insurance practices to ensure compliance with the UUPK. Intensive education for the public regarding consumer rights and obligations is also very necessary to increase legal awareness and prevent conflicts. In addition, strict law enforcement through judicial institutions or the Consumer Dispute Resolution Agency (BPSK) must be implemented to provide maximum protection to consumers and create a transparent, fair, and responsible insurance industry climate.